Characterization of a metagenome-derived protease from contaminated agricultural soil microorganisms and its random mutagenesis - Jiang, Chengjian; Zhang, Liang; Li, Fajia; Meng, Can; Zeng, Rong; Deng, Jie; Shen, Peihong; Ou, Qian; Wu, Bo (Folia microbiologica, 2017)
Proteases are typical key enzymes that hydrolyze proteins into amino acids and peptides. Numerous proteases have been studied, but the discovery of metagenome-derived proteases is still significant for both commercial applications and basic research. An unexplored protease gene sep1A was identified by function-based screening from a plasmid metagenomic library derived from uncultured contaminated agricultural soil microorganisms. The putative protease gene was subcloned into pET-32a (+) vector and overexpressed in E. coli BL21(DE3) pLysS, then the recombinant protein was purified to homogeneity. The detailed biochemical characterization of the Sep1A protein was performed, including its molecular characterization, specific activity, pH-activity profile, metal ion-activity profile, and enzyme kinetic assays. Furthermore, the protein engineering approach of random mutagenesis via error-prone PCR was applied on the original Sep1A protein. Biochemical characterization demonstrated that the purified recombinant Ep48 protein could hydrolyze casein. Compared with the original Sep1A protein, the best variant of Ep48 in the random mutagenesis library, with the Gln307Leu and Asp391Gly changes, exhibited 2.62-fold activity at the optimal reaction conditions of 50 °C and pH 9.0. These results are the first step toward a better understanding of the properties of Sep1A protein. Protein engineering with error-prone PCR paves the way toward the metagenome-derived genes for biotechnological applications.
Keywords: molekulární sekvence - údaje; bakteriální proteiny; sekvenční seřazení; kinetika; klonování DNA; Bacteria; Molecular Sequence Data; stabilita enzymů; půdní mikrobiologie; Cloning, Molecular; genová knihovna; Enzyme Stability; Metagenome; metagenom; mutageneze; sekvence aminokyselin; Amino Acid Sequence; Temperature; proteasy; Sequence Alignment; Gene Library; Kinetics; Mutagenesis; Soil Microbiology; Peptide Hydrolases; Bacterial Proteins; teplota